(untitled) (Eurasian Journal of Ecology, 2016)
Mangistau region is one of the main areas of hydrocarbon production , where large marine and terrestrial oil deposits . In addition to the region’s many flooded wells , which pose a real danger to the environment , focusing mainly on the peninsula Buzachi and especially in the area Karajanbas . Describes the ecological condition of flooded wells oilfields Mangistau region in seawater and sediments.